2020
DOI: 10.1038/s41467-020-18390-z
|View full text |Cite
|
Sign up to set email alerts
|

Wood hemicelluloses exert distinct biomechanical contributions to cellulose fibrillar networks

Abstract: Hemicelluloses, a family of heterogeneous polysaccharides with complex molecular structures, constitute a fundamental component of lignocellulosic biomass. However, the contribution of each hemicellulose type to the mechanical properties of secondary plant cell walls remains elusive. Here we homogeneously incorporate different combinations of extracted and purified hemicelluloses (xylans and glucomannans) from softwood and hardwood species into self-assembled networks during cellulose biosynthesis in a bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(90 citation statements)
references
References 91 publications
1
78
0
1
Order By: Relevance
“…[ 129–131 ] In comparison, the content of cellulose in wood only accounts for 40–50% by atom ratio, along with 10–30% hemicellulose and 20–30% lignin. [ 132–135 ] Recently, Li et al. investigated the impact of pyrolysis temperature on the storage performance of Li + ions in pyrolytic‐polyvinylidene fluoride (PVDF)‐coated hard carbons derived from pure cellulose.…”
Section: Classification and Optimization Strategies Of Hard Carbonsmentioning
confidence: 99%
“…[ 129–131 ] In comparison, the content of cellulose in wood only accounts for 40–50% by atom ratio, along with 10–30% hemicellulose and 20–30% lignin. [ 132–135 ] Recently, Li et al. investigated the impact of pyrolysis temperature on the storage performance of Li + ions in pyrolytic‐polyvinylidene fluoride (PVDF)‐coated hard carbons derived from pure cellulose.…”
Section: Classification and Optimization Strategies Of Hard Carbonsmentioning
confidence: 99%
“…The exact biological functions of conifer hemicelluloses are still debated. However, they are likely to mediate cross‐linking of different cell wall components and modulate the mechanical properties of the cell wall (Terrett & Dupree, 2019; Berglund et al ., 2020a,b; Martínez‐Abad et al ., 2020). Both in vitro binding assays (Whitney et al ., 1998; Berglund et al ., 2020a,b) and in planta analysis (Terashima et al ., 2009; Yu et al ., 2018; Terrett et al ., 2019) suggest that GGM can interact with cellulose microfibrils.…”
Section: Introductionmentioning
confidence: 99%
“…For the samples treated from 160 ℃ to 200 ℃, the intensities of the two split peaks decreased upon increasing the temperature, which indicated that the elastic-like response of cellulose and the stiffness of thermally-treated wood were decreased (Hofstetter et al, 2006; Åkerholm and Salmén 2003). The main reason for this was that the hemicelluloses, as the micro brilmatrix interface, crosslinked on the surface of the micro brils, which increased the stiffness of the cell wall (Berglund 2020). This was also demonstrated by the relationship between the hemicellulose content and elastic modulus of thermally-treated wood (Kačíková et al, 2013), but for the sample treated at 220 ℃, the intensities of the two split peaks increased, which indicated that the stiffness of the sample increased because the MFA decreased (Table 1).…”
Section: Results Of Dynamic Ftirmentioning
confidence: 99%